NKG2A blockade potentiates CD8 T-cell immunity induced by cancer vaccines - Montfoort, Nadine van; Borst, Linda; Korrer, Michael J.; Sluijter, Marjolein; Marijt, Koen A.; Santegoets, Saskia J.; van Ham, Vanessa J.; Ehsan, Ilina; Charoentong, Pornpimol; André, Pascale; Wagtmann, Nicolai; Welters, Marij J.P.; et al. (Cell, 2018)
Tumor-infiltrating CD8 T cells were found to frequently express the inhibitory receptor NKG2A, particularly in immune-reactive environments and after therapeutic cancer vaccination. High dimensional cluster analysis demonstrated that NKG2A marks a unique immune effector subset preferentially co-expressing the tissue-resident CD103 molecule, but not immune checkpoint inhibitors. To examine if NKG2A represented an adaptive resistance mechanism to cancer vaccination, we blocked the receptor with an antibody and knocked out its ligand Qa-1b, the conserved ortholog of HLA-E, in four mouse tumor models. The impact of therapeutic vaccines was greatly potentiated by disruption of the NKG2A/Qa-1b axis, even in a PD-1 refractory mouse model. NKG2A blockade therapy operated through CD8 T cells, but not NK cells. These findings indicate that NKG2A-blocking antibodies might improve clinical responses to therapeutic cancer vaccines.,
Gesehen am 19.03.2020